Start by writing down your starting expression
E = (6x^2 - 54x + 84)/(8x^2 - 40x + 48) * (x^2 + 12x + 32)/(x^2 + x - 56)
For the first fraction, you can factor the numerator by 6 and the denominator by 8 to get
E = (6 * (x^2 - 9x + 14))/(8 * (x^2 - 5x + 6)) * (x^2 + 12x + 32)/(x^2 + x - 56)
All these quadratics can be easily factored by using the sum/product technique to get
x^2 - 9x + 14 = x^2 - 2x - 7x + 14 = (x-2)(x-7)
x^2 - 5x + 6 = x^2 - 2x - 3x + 6 = (x-2)(x-3)
x^2 + 12x + 32 = x^2 + 4x + 8x + 32 = (x+ 8)(x + 4)
x^2 + x - 56 = x^2 + 8x - 7x + 56 = (x+8)(x-7)
The expression will thus be equal to
E = (6 * color(red)(cancel(color(black)((x-2)))) * color(green)(cancel(color(black)((x-7)))))/(8 * color(red)(cancel(color(black)((x-2)))) * (x-3)) * (color(blue)(cancel(color(black)((x+8)))) * (x+4))/(color(blue)(cancel(color(black)((x+8)))) * color(green)(cancel(color(black)((x-7)))))
E = color(green)(3/4 * (x+4)/(x-3)